cDNA isolation and expression of nicotinamide adenine dinucleotide phosphate-dependent cytochrome P450 reductase gene in the Chagas disease vector Triatoma infestans - Grosso, Carla Gisela; Stroppa, María Mercedes; García, Beatríz Alicia; Varela, Gonzalo Matías (American Society of Tropial Medicine and Hygiene, 2023)
7 p.